Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5194/se-8-955-2017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sediment loading in Fennoscandia and the Barents Sea during the last glacial cycle on glacial isostatic adjustment observations

Abstract: Abstract. Models for glacial isostatic adjustment (GIA) routinely include the effects of meltwater redistribution and changes in topography and coastlines. Since the sediment transport related to the dynamics of ice sheets may be comparable to that of sea level rise in terms of surface pressure, the loading effect of sediment deposition could cause measurable ongoing viscous readjustment. Here, we study the loading effect of glacially induced sediment redistribution (GISR) related to the Weichselian ice sheet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The importance of SIA effects on RSL modeling in the Indus River basin and Arabian Sea has been demonstrated by Ferrier et al (2015), who found that the perturbation to current rates of change of RSL in the region caused by sediment fluxes is nonnegligible. A recent study (Van der Wal & IJpelaar, 2017) applied the sea level theory of Dalca et al (2013) to examine the influence of glacially induced sediment redistribution to modeled observables in Fennoscandia for the last glacial cycle. They found that while the effects on RSL and uplift rates were relatively small (few meters for Holocene RSL; order of a tenth of a mm/yr for present-day uplift rates), they represent a significant bias to the modeled signal.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of SIA effects on RSL modeling in the Indus River basin and Arabian Sea has been demonstrated by Ferrier et al (2015), who found that the perturbation to current rates of change of RSL in the region caused by sediment fluxes is nonnegligible. A recent study (Van der Wal & IJpelaar, 2017) applied the sea level theory of Dalca et al (2013) to examine the influence of glacially induced sediment redistribution to modeled observables in Fennoscandia for the last glacial cycle. They found that while the effects on RSL and uplift rates were relatively small (few meters for Holocene RSL; order of a tenth of a mm/yr for present-day uplift rates), they represent a significant bias to the modeled signal.…”
Section: Introductionmentioning
confidence: 99%
“…Dalca et al (2013) were the first to incorporate the gravitational, deformational, and rotational effects of sediment redistribution into a traditional GIA model (Figure 7a). The resulting theory has been used to 620 demonstrate that the impact of sediment erosion and deposition, associated with both fluvial and glacial systems, can alter relative sea-level by several metres over the course of a glacial cycle and rates of present-day deformation by a few tenths of a mm/yr (Wolstencroft et al, 2014;Ferrier et al, 2015;Kuchar et al, 2017;van der Wal and IJpelaar, 2017 magnitude of the perturbation due to sediment loading is small, it is greater than the precision of modern geodetic methods, and hence has the potential to bias contemporary estimates of sea-level change (Ferrier et al, 2015;van der Wal and IJpelaar, 625 2017). Perhaps the most important finding of these preliminary studies is the observation that in order for relative sea-level indicators to be used to constrain past global ice volumes, they must first be corrected for the effects of both glacial and sedimentary isostasy (Ferrier et al, 2015).…”
Section: Sedimentary Isostasy 615mentioning
confidence: 99%
“…Similarly, global ice volumes may be incorrectly inferred if viscosity variations are ignored at far-field sea-level sites (Austermann et al, 2013). If the past ice history of a region has been independently determined then neglect of lateral variations in Earth structure will lead to bias in predictions of the GIA signal, and hence bias in estimates of contemporary ice sheet mass balance, potentially on the order of 10's Gt/a (van der Wal et al, 2015). Furthermore, models that consider the coupled evolution of the ice sheet-solid Earth system (see Sect.…”
Section: Lateral Variations In Earth Rheology and Non-linear Rheologymentioning
confidence: 99%
“…Dalca et al (2013) were the first to incorporate the gravitational, deformational, and rotational effects of sediment redistribution into a traditional GIA model (Figure 7a). The resulting theory has been used to demonstrate that the impact of sediment erosion and deposition, associated with both fluvial and glacial systems, can alter relative sea-level by several metres over the course of a glacial cycle and rates of present-day deformation by a few tenths of a mm/a (Wolstencroft et al, 2014;Ferrier et al, 2015;van der Wal and IJpelaar, 2017;Kuchar et al, 2017). Although the magnitude of the perturbation due to sediment loading is small, it is greater than the precision of modern geodetic methods, and hence has the potential to bias contemporary estimates of sea-level change (Ferrier et al, 2015;van der Wal and IJpelaar, 2017).…”
Section: Sedimentary Isostasymentioning
confidence: 99%
See 1 more Smart Citation